2018
DOI: 10.1021/acsami.8b20821
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Nanoassembly of Bioengineered Chitosan-Modified FcRn-Targeted Porous Silicon Nanoparticles @ Hypromellose Acetate Succinate for Oral Delivery of Antidiabetic Peptides

Abstract: Microfluidics technology is emerging as a promising strategy in improving the oral delivery of proteins and peptides. Herein, a multistage drug delivery system is proposed as a step forward in the development of noninvasive therapies. Undecylenic acid-modified thermally hydrocarbonized porous silicon (UnPSi) nanoparticles (NPs) were functionalized with the Fc fragment of immunoglobulin G for targeting purposes. Glucagon-like peptide-1 (GLP-1) was loaded into the NPs as a model antidiabetic drug. Fc-UnPSi NPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 54 publications
(149 reference statements)
3
47
0
Order By: Relevance
“…3D, an uptake of over 40% of the chitosan-coated liposomes was observed, whereas no uptake was detected for liposomes without chitosan. This phenomenon was also observed in previous works 69,87 and it might be related to the chitosan mucoadhesion properties, driven by the electrostatic interactions between the positive charge of the chitosan and the negative charge of mucins. 88…”
Section: Biomaterials Science Communicationsupporting
confidence: 83%
See 1 more Smart Citation
“…3D, an uptake of over 40% of the chitosan-coated liposomes was observed, whereas no uptake was detected for liposomes without chitosan. This phenomenon was also observed in previous works 69,87 and it might be related to the chitosan mucoadhesion properties, driven by the electrostatic interactions between the positive charge of the chitosan and the negative charge of mucins. 88…”
Section: Biomaterials Science Communicationsupporting
confidence: 83%
“…Regarding the pH-responsiveness of MF-based microparticles, TEM imaging and the size measurement over the time have shown that MF microparticles remain intact at pH 1.2, but upon pH increase to 6.8, the enteric polymer starts to dissolve, releasing the CHT-based NPs, and after 2 h, the polymer is completely dissolved. [67][68][69] With respect to the pH of the small intestine in the fed or fasted state, McConnell et al reported that the fed state of the animal (rats or mice) had no significant effect on the pH. 70 Thus, it is hypothesized that the insulin release might not be affected by food intake, although this needs to be still confirmed in the future for our particular system.…”
mentioning
confidence: 88%
“…Thus, there is a need to make a quantum leap in the design of drug-encapsulated nanosystems to make oral delivery far more efficient. One way to achieve this may be to combine the biotechnological advances of NP design with strategies to target FcRn at mucosal surfaces [11][12][13][14][15]. This may allow active transport across the polarized intestinal epithelium for delivery to the systemic circulation [11,12,15].…”
Section: Fcrn-targeted Nanosystems For Oral Delivery Of Antidiabetic Peptidesmentioning
confidence: 99%
“…However, the transport of NPs across intestinal mucosa is restricted by polarized epithelial cell layers [8,10]. Several recent studies support that targeting of the neonatal Fc receptor (FcRn), which is expressed by such epithelial cells and mediates bidirectional transport and recycling of immunoglobulin G (IgG) and albumin, may be used as a gateway for more efficient transcellular transport of NPs [11][12][13][14][15]. Furthermore, in light of successes in the development of engineered ligands and alternative scaffolds with improved FcRn binding and transport properties, researchers may now harvest from these advances in the design of new classes of NPs decorated with FcRn-targeted molecules, with the aim of enhancing transmucosal delivery upon oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…PSi micro/nano‐particles have been extensively investigated for drug delivery in the treatment of cancer, diabetes, and cardiovascular diseases. [ 27–33 ] Moreover, the material itself presents immunomodulatory properties due to the surface modification, which render it an attractive candidate as nanovaccine platform for cancer immunotherapy or for autoimmune diseases. [ 2,12,34 ] The coating with cell membrane moieties can thereby improve the circulation time, slow the recognition by the cells of the mononuclear phagocyte system, and act as source of antigens and danger signals.…”
Section: Introductionmentioning
confidence: 99%